PENGARUH KUALITAS PELAYANAN DAN CITRA INSTITUSI TERHADAP KEPUASAN PASIEN PUSKESMAS ADIARSA KARAWANG - Gina Syahrini; Dadan Ahmad Fadili (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine, analyze and explain whether service quality and agency image partially or simultaneously affect patient satisfaction at the Adiarsa Karawang Public Health Center. This study uses quantitative methods of descriptive analysis and verification, namely collecting, presenting, analyzing, testing hypotheses, providing conclusions and suggestions. The sample in this study used incidental sampling technique with incidental sampling method as many as 273 people using Likert scale technique and path analysis. The results showed that the correlation between service quality and institutional image was 0.845, which means the correlation is strong, positive and significant. The partial effect of service quality on patient satisfaction is 17.1%. The partial effect of institutional image on patient satisfaction gets a value of 68.4%. The simultaneous influence of Service Quality and Institutional Image on patient satisfaction obtained a value of 85.5%, the remaining 14.5% was influenced by other variables not examined